Performance Analysis of PCFICH and PDCCH LTE Control Channels - Milos, Jiri; Hanus, Stanislav (Společnost pro radioelektronické inženýrství, 2014)
Control channels play a key role in the evaluation of mobile system performance. The purpose of our paper is to evaluate the performance of the control channels implementation in the Long Term Evolution (LTE) system. The paper deals with the simulation of the complete signal processing chain for Physical Control Format Indicator Channel (PCFICH) and Physical Downlink Control Channel (PDCCH) in the LTE system, Release 8. We implemented a complete signal processing chain for downlink control channels as an extension of the existing MATLAB LTE downlink simulator. The paper presents results of PCFICH and PDCCH control channel computer performance analysis in various channel conditions. The results can be compared with the performance of data channels.
Keywords: Long Term Evolution; Release 8; control channels; Physical Control Format Indicator Channel; Physical Downlink Control Channel; MATLAB; link level simulator